(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Internet is the essential tool of transmitting information and providing services to facilitate the human daily jobs. The internet has a great impact on various fields of life, including learning, where e-learning emerged as one of the services provided by the Internet. E-learning is a distance knowledge acquisition by using electronic methods and it has increased dependence in the two decades ago. One of the problems facing e-learning is contents management because E-learning differs from traditional learning by overcoming the conditions of time and place. The semantic web is the restructuring of the current web to managing data and resources to become more effective for human and machine. The semantic web is based on an ontology which is defined as a descriptive representation of data and resources. It is expected that Semantic Web technologies and Ontologies will affect the next generation of e-learning systems and applications. Resource Description Framework (RDF) is a general modeling for data representation by using a variety of syntax. A friend of a friend (FOAF) and Dublin Core (DC) are a vocabulary description depending on RDFs’ rules. This paper presents a semantic management of E-learning in College of Engineering at University of Kerbala based on ontology of users’ profile, scientific activities, and lessons. RDF, FOAF, and DC are used to create a syntax of metadata. The proposed work was evaluated according to average precision and recall of the search’s results and social network metrics. The results demonstrate that FOAF is a good way to represent nodes and relations and this improves using it in searching without access the database. FOAF has the ability to gathering dispersed data into common interests.